2022
DOI: 10.3389/fvets.2022.947154
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of methicillin-resistant Staphylococcus aureus in dairy farms: A systematic review and meta-analysis

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is an opportunistic bacterium that causes many human and animal infections worldwide. MRSA infections are classified as priority infections owing to their high morbidity and mortality, with a significant risk of zoonotic transmission. This study aimed to determine the pooled prevalence of MRSA in dairy cattle farms and its heterogeneity. Relevant studies were retrieved from three databases: PubMed, Web of Science, and Scopus. The pooled prevalence of MRSA in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 116 publications
2
4
1
Order By: Relevance
“…throughout eight farms and two retail supermarkets. Surprisingly, no isolates were identified as S. aureus, which contrasts with other studies that have found an overall prevalence of 3.81% in dairy farms, 4%-46.6% in bulk tank milk, and 22.5%-47% in meat and poultry (Abdalrahman et al, 2015;Bhargava et al, 2011;Haran et al, 2012;Khanal et al, 2022;Patel et al, 2021;Waters et al, 2011). Instead, this study found that the Staphylococci isolates, which include both identified and unknowns, were CNS, falling within the overall prevalence of 9.6%-26% found in similar studies done on dairy farms (Condas et al, 2017;Gizaw et al, 2020).…”
Section: Discussioncontrasting
confidence: 97%
“…throughout eight farms and two retail supermarkets. Surprisingly, no isolates were identified as S. aureus, which contrasts with other studies that have found an overall prevalence of 3.81% in dairy farms, 4%-46.6% in bulk tank milk, and 22.5%-47% in meat and poultry (Abdalrahman et al, 2015;Bhargava et al, 2011;Haran et al, 2012;Khanal et al, 2022;Patel et al, 2021;Waters et al, 2011). Instead, this study found that the Staphylococci isolates, which include both identified and unknowns, were CNS, falling within the overall prevalence of 9.6%-26% found in similar studies done on dairy farms (Condas et al, 2017;Gizaw et al, 2020).…”
Section: Discussioncontrasting
confidence: 97%
“…Interestingly, our study carriage of mec was significantly lower in dairy compared to all other foods and clinical sources (Figure 3, Supplementary File S2). This finding is similar to a meta-analysis conducted by Khanal et al [91], who reported the prevalence of MRSA to be 3.81% overall and 3.91% in dairy cattle farms and cattle milk specifically. While MRSA isolates are commonly recovered from foods, the role of food in their transmission remains unclear [92].…”
Section: Filling the Gaps In Agri-food Testing And Resistance Surveil...supporting
confidence: 91%
“…The low numbers of oxacillin resistance of all Staphylococcal species in this study is in contrast to what is seen in small animal medicine in which an increase has been seen in oxacillin resistance in dogs in recent years [ 32 , 33 , 34 ]. However, the low prevalence of oxacillin resistance seen in this study is similar to that seen in livestock [ 35 ]. It is hypothesized that there is less methicillin/oxacillin resistance in livestock and horses when compared to small animals due to the increased regulations on antibiotic use and decreased available antibiotics for use in the large animal species.…”
Section: Discussionsupporting
confidence: 63%